(3GJMGa GdhQi HCNHGQ Ce GdbQis - (3GHf agO , YeQ Hf eMeO Hf eMeO Hf CHj GdNjQ eMeO Hf eMeO Hf YHO Gddg Hf agO GdbQTj GdgGTej, CHj GdNjQ , fLe GdOjf,J (B885 (3g` s ((3ecI GdecQI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdOfjG eVeGQ GdNdbI hHYO aEf Yde GdJGQjN dGTc ai LdGdI bOQg s
(3BNQgG (B:s
(3hSJjJ HfJ GdbGVi LeGd GdOjf Hf fLe GdOjf Hf XgjQI RhLI GdbGVi LeGd GdOjf CHh GdSYhO Hf XgjQI VMi jhe GdKdGKGA NGeS TYHGf hUdi YdjgG YUQ jhegG BNQ GJMGa GdhQi s
(3GdfSNI efbhdI Yf fSNI HNW GdeDdas
(3HgG fXGe GdJYbjHIs
(3jJVef GdeNWhW PcQ MhGOK ecI hCNHGQgG hhajGJ CgdgG eQJH Ydi GdSff GHJOGA ef hdGOI GdQShd Udi Gddg Ydjg hSde hjfJgi Edi hajGJ (B885 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B318s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs